ISLAMIC ART AND THE MUSEUM : Approaches to Art and Archeology of the Muslim World in the Twenty-First Century - Junod, Benoit,; Khalil, Georges,; Weber, Stefan (Director of the Museum of Islamic Art),; Wolf, Gerhard, (Saqi Books, 2012)
Museums covered in detail include the David Collection, Brooklyn Museum's Arts of the Islamic World Galleries, Museum of Islamic Art in Doha, Hermitage Museum, British Museum, Aga Khan Museum in Toronto and the Museum of Islamic Art at the Pergamon Museum.